2017
DOI: 10.1103/physreve.95.012107
|View full text |Cite
|
Sign up to set email alerts
|

Frequency regulators for the nonperturbative renormalization group: A general study and the model A as a benchmark

Abstract: We derive the necessary conditions for implementing a regulator that depends on both momentum and frequency in the nonperturbative renormalization group flow equations of out-of-equilibrium statistical systems. We consider model A as a benchmark and compute its dynamical critical exponent z. This allows us to show that frequency regulators compatible with causality and the fluctuationdissipation theorem can be devised. We show that when the Principle of Minimal Sensitivity (PMS) is employed to optimize the cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 57 publications
2
55
0
Order By: Relevance
“…Furthermore, it is also found that the dynamical critical exponent in a relativistic O(N ) vector model is close to 2 [63]. Similar result is also found for the O(3) model in [75]. In summary, whether the critical dynamics of the relativistic O(4) scalar theory falls into Model A or Model G is still an open question, and more insightful studies are required.…”
Section: Dynamical Critical Exponentsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, it is also found that the dynamical critical exponent in a relativistic O(N ) vector model is close to 2 [63]. Similar result is also found for the O(3) model in [75]. In summary, whether the critical dynamics of the relativistic O(4) scalar theory falls into Model A or Model G is still an open question, and more insightful studies are required.…”
Section: Dynamical Critical Exponentsupporting
confidence: 69%
“…But if the regulator in Equation ( 17) is extended to the one having a finite imaginary part, as done in some nonequilibrium calculations, e.g. [75], a nonvanishing qq-component of regulators is necessary. With the regulator in Equation ( 21), one can reformulate the flow equation for the effective action in Equation (113) as such…”
Section: The O(n ) Scalar Theory Within the Real-time Frg Approachmentioning
confidence: 99%
“…However, in the range 1/4 ≤ θ < 1/2, an ambiguity arises in the second term, since this term vanishes only if the limit → 0 is taken before the integration on ω. This ambiguity is present because the frequency sector is not properly regularized, and would disappear with a frequency-dependent regulator [62]. Since the result should not depend on the choice of the regulator, we simply assume that this term is zero since it would vanish with a frequency regulator.…”
Section: Discussionmentioning
confidence: 99%
“…The process is the same as above, except that the temperature immediately after t = 0 is now the Curie temperature: In this situation, the correlation length still grows as a power law, ξ(t) ∼ t 1 /zc , with z c ≈ 2.17 the critical dynamical exponent [52,13,53,54]. The growth of the correlation length is slightly slower than in the previous situation since 1 /z c ≈ 0.461 < 1 /2.…”
Section: Quench To T = T Cmentioning
confidence: 95%